Lithium contamination of honeybee products and its accumulation in brood as a consequence of anti-varroa treatment. (15th November 2020) - Prešern, Janez; Kur, Uroš; Bubnič, Jernej; Šala, Martin
Highlights: Lithium chloride is an emergent varroa control substance in beekeeping. Lithium has an impact on both human well-being and honeybee health. There is risk of lithium entering human food chain inadvertently. Lithium accumulates in honeybee products such as pollen and honey. Lithium accumulates in honeybee brood and increases mortality in adults. Abstract: Varroa destructor, the primary honeybee pathogen, is kept in check by various chemical compounds which may enter the human diet through honeybee products. Lithium is an emerging varroa control substance, and we investigated its accumulation in honey, bee bread, brood and adults along with the mortality of bees. Increased lithium concentrations were detected in workers, fed individually once per os with 10 µL of 25 mM LiCl in sucrose solution (6.50–40.10 mg/kg) or had the same solution available ad libitum (39.25–266.00 mg/kg). A three-day treatment of honeybee colonies with 25 mM LiCl in 1L/day sucrose solution increased lithium concentrations in five-day-old larvae, honey, and bee bread: up to 45.0, 1.2, and 47.0 mg/kg, respectively. Lithium concentrations peaked three days post-treatment in both larvae and honey and increased worker mortality was observed. The control colonies exhibited lithium concentrations below the limit of quantification (0.5 mg/kg). Prudence in lithium use is advised.